PENGARUH KUALITAS LAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING (STUDI PADA BANK BSI AREA BASUKI RAHMAT SITUBONDO) - Hidayatullah, Ahmad; Ediyanto, Ediyanto; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of the study was to determine the effect of service quality and trust on customer loyalty with satisfaction as an intervening variable (study at BSI Bank Area Basuki Rahmat Situbondo). The sampling technique used in this study is a saturated sample. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results showed that Service Quality had a positive and significant effect on Customer Satisfaction, Trust had a positive and significant effect on customer satisfaction, Service Quality had a positive and significant effect on Customer Loyalty, Trust had a positive and significant effect on Customer Loyalty, Customer Satisfaction had a positive and significant effect on Loyalty. Customers, Service Quality has a positive but not significant effect on Customer Loyalty through Customer Satisfaction, Trust has a positive but not significant effect on Customer Loyalty through Customer Satisfaction